Oxidative Stress Status in Testis of Type-2 Diabetic Rats Treated with Delta-9-Tetrahydrocannabinol - Ebrar Tatar; Beti Pesen; Zeynep Mine Coşkun Yazıcı; Sema Bolkent (European Journal of Biology)
Objective: Type-2 diabetes (T2D) is a multifactorial disease that occurs as a result of impaired insulin secretion and increased glucose. Researchers emphasize that oxidative stress prevention and improvement strategies are important in the general treatment of T2D. It is reported that delta-9-tetrahydrocannabinol (THC), a component of the cannabis plant, has positive effects against oxidative stress and inflammation. Therefore, this study explored the inhibitory effects of THC on oxidative damage of testis in type-2 diabetic rats. Materials and Methods: Adult Spraque-Dawley rats were separated into 4 groups. In the control group, physiological saline was given intraperitoneally. In the T2D model group (T2DM), streptozotocin (STZ) + nicotinamide (NAD) was administered intraperitoneally. Three mg/kg/day THC was given to the THC and T2DM+THC groups for 7 days, intraperitoneally. Glutathione (GSH), malondialdehyde (MDA), and protein carbonyl levels (PCO), and superoxide dismutase (SOD) activity were measured spectrophotometrically in testicular tissue. Total oxidant and antioxidant status were determined by ELISA. Results: Testicular GSH level and SOD activity were significantly decreased in T2D, while MDA and PCO levels increased. In contrast to this effect, the THC treatment increased GSH levels and SOD activity in diabetics, but decreased MDA and PCO levels. Conclusion: According to the study results, THC may have an oxidative stress inhibitory effect on diabetic rat testis.